Students' acceptance and use of interactive whiteboard - Norsyarfarina Mokhtar; Heerashini Baithma Jothi; Rosalia Joan Gilos; Gayathri Gunabalan; Rimalyn Jalila; Nur Maisarah Mohamad; Dofina Angil Jimmy (IGI Global, 2016)
The aim of this research is to examine the acceptance and use of interactive whiteboards among universities students. The research implements a hierarchical regression for statistics analysis over sample of research consists of 204 respondents, who have participated voluntarily for research purposes. The results show that performance expectancy, effort expectancy, and social influence positively effecting the behavioral intention. However, facilitating condition has negative impact on the acceptance of interactive whiteboard. University management and lecturers may gain further understanding and knowledge about the interactive whiteboard towards students. The results also provide insights for university management in improving the knowledge of students by giving more guidance, learning process and more practice of the usage during classes and presentations to improve the students understanding and make them learn more so it will benefit them in their future.